ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA INSPEKTORAT KOTA TOMOHON - Ilat, Cicilia; Saerang, David P.E. (Universitas Sam Ratulangi, 2015)
The results based on a count coefficient for the linear regression equation by 0.639. This suggests that in this equation the model of 0.639 explained by the influence of the independent variables (the competence, independence and experience) on the dependent variable (performance inspectorate), while the remaining 36.1% is explained by other factors that are not included in this model , After testing the hypothesis with the t-test, it was concluded that the independence (X2) and experience (X3) significantly affect the performance of the inspectorate, while competence does not significantly affect the performance of the inspectorate. Furthermore, the F-test, showed that competence (X1), independence (X2) and experience (X3) jointly affect the performance of the inspectorate. The degree of influence of each variable appears in the regression coefficient that is competence (X1) of 0.059; independence (X2), amounting to 0.748 and the regression coefficient of variable experience (X3) of 1.087.Implikasi findings of this study is to boost the performance of inspectorates to create good financial management with efforts to increase the independence, experience for inspectorates and with due regard to the competence of the inspectorate as a qualification for functional inspectorate. Increased capacity, all three factors the results of this study need to be done jointly for mutually complementary.